The Turkish Constitutional Court, laicism and the headscarf issue - Oztig, Lacin Idil (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2018)
From 1989 onwards, the Turkish Constitutional Court justified the headscarf ban in universities by citing laicism. Interestingly, in 2014, the Court found the headscarf ban in courts unconstitutional and revoked it by again citing laicism as the main reason. How can this seemingly paradoxical practice be explained? This article traces the trajectory of the headscarf issue in Turkey by analysing and contextualising the Constitutional Court decisions. In order to explain how and why the Constitutional Court issued two opposing views of the headscarf ban, this article focuses on the changing political climate and legal developments that took place in Turkey between 2008 and 2014.
Keywords: Turkey; the headscarf issue; laicism; religious freedom; SECULARISM; RELIGION; SOCIETY; POLITICS; Development Studies